KEPEMIMPINAN VISIONER DALAM PENDIDIKAN ISLAM: STRATEGI MEMBANGUN BUDAYA ORGANISASI BERBASIS AKHLAK - Nur Ismiyahyi; Ali Nasith (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2026)
Islamic education essentially carries a dual mission: to produce a generation that excels academically while also being morally and spiritually strong. The reality in many Islamic educational institutions shows that leadership orientation is more dominated by a focus on administrative achievements and quantitative indicators rather than character building and spiritual values. This condition has resulted in a crisis of vision that threatens the identity and relevance of Islamic education. Visionary leadership in Islamic educational institutions plays a crucial role in realizing national learning objectives and producing high-quality, visionary human resources capable of responding to the challenges of the times. This study aims to analyze visionary leadership in building an ethics-based organizational culture within Islamic educational institutions. The method employed in this study is a literature review, with data collection conducted through books, articles, journals, and other sources to identify relevant information regarding visionary leadership, ethical values, and ethics-based organizational culture. The results of the study indicate that the role of visionary leaders serves as a guide in building an Islamic ethics-based organizational culture. The strategy for building this organizational culture involves integrating the four functions of management with ethical values such as shidiq (truthfulness), amanah (trustworthiness), fhathanah (wisdom), and tabligh (communication). Implementing an ethics-based organizational culture within Islamic educational institutions can foster harmonious internal relationships within the institution.